RUSSIAN EXPERIENCE IN ENGINEERING EDUCATION DEVELOPMENT - A. I. RUDSKOY; A. I. BOROVKOV; P. I. ROMANOV (Moscow Polytechnic University, 2018)
The implementation of the large-scale system program devoted to the development of a new technological generation economy announced by the President of Russia V.V. Putin in his Address to the Federal Assembly of the Russian Federation on December 1, 2016 brings new challenges to the system of engineering education in Russia. The Coordinating Council in Educational Sphere "Engineering, Technology and Technical Sciences" works out a strategy for the development of engineering education in Russia for the period until 2020, based on the need to face up new challenges. The solution of these tasks is impossible without a broad public and professional discussion based on the analysis of the history of engineering education development in Russia and in the USSR, its achievements and problems of modern engineering education, materials and documents on public policy in this field. This article attempts to analyze the relationship between engineering education development and the tasks of Russia's economic, geopolitical development in different historical periods.